2019
DOI: 10.1007/s12975-019-00742-7
|View full text |Cite
|
Sign up to set email alerts
|

Progression and Classification of Granular Osmiophilic Material (GOM) Deposits in Functionally Characterized Human NOTCH3 Transgenic Mice

Abstract: CADASIL is a NOTCH3-associated cerebral small vessel disease. A pathological ultrastructural disease hallmark is the presence of NOTCH3-protein containing deposits called granular osmiophilic material (GOM), in small arteries. How these GOM deposits develop over time and what their role is in disease progression is largely unknown. Here, we studied the progression of GOM deposits in humanized transgenic NOTCH3 Arg182Cys mice, compared them to GOM deposits in patient material, and determined whether GOM deposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…45,47,51,52 In agreement with this notion, the number, size, and morphology of GOM deposits evolve through the course of the disease. 53 In vitro studies have demonstrated reduced clearance and decreased solubility of mutant Notch3 protein complexes compared with wild Notch3 in Small-Vessel Disease…”
Section: Proposed Mechanisms and Supporting Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…45,47,51,52 In agreement with this notion, the number, size, and morphology of GOM deposits evolve through the course of the disease. 53 In vitro studies have demonstrated reduced clearance and decreased solubility of mutant Notch3 protein complexes compared with wild Notch3 in Small-Vessel Disease…”
Section: Proposed Mechanisms and Supporting Evidencementioning
confidence: 99%
“…66 Conversely, a different CADASIL mouse model overexpressing high levels of mutant Notch3, the tgN3 MUT 350 mouse, presented important GOM deposition but failed to develop other central disease features, including mural cell degeneration, basement membrane thickening, or changes in cerebrovascular reactivity and cognition. 53,58 The apparent lack of robust association between GOM and vessel structural or functional integrity in animal studies might be secondary to limitations of current animal models in accurately replicating the full spectrum of CADASIL pathophysiological mechanisms or of methods to detect and quantify GOM in these models.…”
Section: Existing Debate and Diverging Evidencementioning
confidence: 99%
“…The authors found a progression from initially small round GOMs, located to the abluminal side of mural cells, to large amorphous deposits which induced basement membrane bulging and mural cell indentation, seen in the last stages of the disease, and proposed a GOM classification system divided into five stages of progression. Notably, both in aged mice and in post-mortem CADASIL brain microvessels, large and amorphic GOM deposits coexisted with small and recent ones, suggesting that GOMs are continuously formed during disease progression (Gravesteijn et al, 2019).…”
Section: Histopathological Findingsmentioning
confidence: 99%
“…However, GOM formation and development over time and their role in disease progression remain largely unknown. A recent study found that GOM deposits are not static, but rather change in terms of size, morphology, and number during disease course in CADASIL transgenic mice (Gravesteijn et al, 2019). The authors found a progression from initially small round GOMs, located to the abluminal side of mural cells, to large amorphous deposits which induced basement membrane bulging and mural cell indentation, seen in the last stages of the disease, and proposed a GOM classification system divided into five stages of progression.…”
Section: Histopathological Findingsmentioning
confidence: 99%
“…TgNotch3 R182C mice, developed by using a BAC clone containing the human NOTCH3 gene and subsequently introducing the R182C variant by two-step Red-mediated recombination, showed progressively increasing age- and NOTCH3 RNA expression level-dependent vascular accumulation of NOTCH3 and GOM deposits, which progress over time and are continuously being formed, without brain parenchyma lesions occurrence [ 65 ]. This finding led authors to realize the “NOTCH3 score” as quantitative biomarker for CADASIL, attempting to transform transgenic CADASIL mice in a proper model for pre-clinical testing of therapeutic approaches [ 66 ].…”
Section: Disease Modelsmentioning
confidence: 99%